2020
DOI: 10.7759/cureus.8198
|View full text |Cite
|
Sign up to set email alerts
|

Two False Negative Test Results in a Symptomatic Patient with a Confirmed Case of Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) and Suspected Stevens-Johnson Syndrome/Toxic Epidermal Necrolysis (SJS/TEN)

Abstract: The recent outbreak of COVID-19 has put significant strain on the current health system and has exposed dangers previously overlooked. The pathogen known as severe acute respiratory syndrome coronavirus 2 (SARS-COV-2), is notable for attacking the pulmonary system causing acute respiratory distress, but it can also severely affect other systems in at-risk individuals including cardiovascular compromise, gastrointestinal distress, acute kidney injury, coagulopathies, cutaneous manifestations, and ultimately dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 14 publications
0
23
0
Order By: Relevance
“…There were single reports with detailed dermatologic information available of petechiae, 78 cherry hemangioma, 19 Raynaud’s, 19 psoriasis flare, 79 nonspecific vesicular rash, 14 acneiform rash, 6 transient acantholytic dermatosis, 40 erythema nodosum, 80 bullous interface dermatitis, 81 pityriasis rosea, 82 Grover’s, 38 digitate papulosquamous eruption, 83 cutaneous small‐vessel vasculitis, 84 oral lesions, 85 and Kawasaki 86 . Of note, for Kawasaki, though the body of literature is growing, cases with detailed dermatologic information are at this time lacking.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were single reports with detailed dermatologic information available of petechiae, 78 cherry hemangioma, 19 Raynaud’s, 19 psoriasis flare, 79 nonspecific vesicular rash, 14 acneiform rash, 6 transient acantholytic dermatosis, 40 erythema nodosum, 80 bullous interface dermatitis, 81 pityriasis rosea, 82 Grover’s, 38 digitate papulosquamous eruption, 83 cutaneous small‐vessel vasculitis, 84 oral lesions, 85 and Kawasaki 86 . Of note, for Kawasaki, though the body of literature is growing, cases with detailed dermatologic information are at this time lacking.…”
Section: Resultsmentioning
confidence: 99%
“…The average age for pediatric patients with a dermatologic manifestation was 12.9 years of age (SD 3.6, or median 14 years with IQR [14, 14]) 11,12,16–18,32,33,52,53,65,66,72,86 and for adults was 34.2 years (SD 21.8, or median 56.8 years with IQR [26, 78]) 5,6,8–15,19,21–26,28–31,34–41,43,45–51,54–61,63,64,67–71,73–77,79–85,88,89 . There was a slight preponderance of females in the pediatric population (57.1%) 12,16–18,32,33,52,53,65,66,72,86 and adult population (52.3%) 5,6,8–15,19,21–26,28–31,34–41,43,45–51,54–61,63,64,67–71,73–77,79–82,84,85,88,89 . Average latency from COVID‐19 symptoms to cutaneous findings for pediatric patients was 1.5 days (SD 2.9, ranging from −3 to 7 days) and for adult patients was 7.9 days (SD 10.7, or median 7 days with IQR [3, 20]), with a range of −2 days (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…It was not reported whether this patient was continued on imatinib or not. Lagziel et al described a 58-year-old woman with a history of CML managed for 4 years with imatinib, morbid obesity, hypertension, gout and chronic kidney disease who was admitted initially for fever and respiratory distress, later complicated by a disseminated erythematous and papular skin rash; biopsy was consistent with bullous interface dermatitis [6] . Using a questionnaire, Li et al studied 530 subjects with CML in Hubei province during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…In genetically predisposed individuals, SARS‐CoV‐2 can trigger the development of a rapid autoimmune and/or autoinflammatory dysregulation and lead to severe interstitial pneumonia 11 . A case report reported that a 58‐year‐old female patient developed SJS and TEN overlap syndrome with COVID‐19 positivity 12 . The pathogenesis of cutaneous symptoms is not understood yet.…”
Section: Characteristics Of Patients % (N)mentioning
confidence: 99%